AN ADAPTIVE CONTROL MODEL FOR LARGE-SCALE GRAPHICAL DATA PROCESSING ON MOBILE DEVICES - Mardankulova Madinaxon Anvarjon qizi (International Journal of Literature and Language Studies, 2026)
This paper proposes an adaptive integrated control model addressing the key deficiency identified in existing solutions for large-scale graphical data processing on mobile devices — namely, the problem of static and isolated resource management. The proposed model formally defines the graphical data flow as a mathematical construct and dynamically adapts rendering parameters based on the real-time device state (GPU load, memory bandwidth, temperature, battery level). The mathematical formulation, optimization function, and theoretical efficiency analysis are presented, along with a comparative evaluation against existing approaches.